2006
DOI: 10.1007/s10856-006-7312-4
|View full text |Cite
|
Sign up to set email alerts
|

Silicone based polyurethane materials: a promising biocompatible elastomeric formulation for cardiovascular applications

Abstract: The biocompatibility of a new material for cardiovascular applications constituted by a poly(ether)urethane (PEtU) and a silicone [polydimethylsiloxane (PDMS)] was evaluated. The achieved material shows properties similar to both polyurethanes and silicones. The material was transformed into porous membranes by a spray-deposition technique. Since any material preparation and manufacturing procedure may introduce some toxicity, in vitro cytotoxicity screening tests were carried out. Human umbilical vein endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 18 publications
3
44
0
2
Order By: Relevance
“…Absorbance values measured considering formazan salt reduction are directly related to cell viability [32,33]. Table 1 shows the average percentage of cell viability at different times of culture with the polymer extract.…”
Section: Resultsmentioning
confidence: 99%
“…Absorbance values measured considering formazan salt reduction are directly related to cell viability [32,33]. Table 1 shows the average percentage of cell viability at different times of culture with the polymer extract.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has already shown the good biocompatibility and mechanical properties of the synthetic layer made of a PEtUePDMS semi-IPN material [29,33].…”
Section: Discussionmentioning
confidence: 99%
“…The PEtUePDMS material containing 30% of PDMS was synthesized according to the previously described protocol [33].…”
Section: Methodsmentioning
confidence: 99%
“…Silicon was introduced into the polyurethane, in order to address the biodegradation problems occurring in long-term implantation. Briganti et al (2006) synthesized silicon based polyurethane materials and studied the biocompatibility of the resulted polyurethane. It was concluded that the incorporation of silicone in the investigated range did not introduce any toxicity into the materials; however, further studies related to biostability and mechanical properties of the new material are necessary.…”
Section: Polyurethane For Cardiovascular Applicationsmentioning
confidence: 99%